1979
DOI: 10.1139/b79-209
|View full text |Cite
|
Sign up to set email alerts
|

Leaf senescence as a factor in the competitive and synergistic interactions of Drechslera sorokiniana and Curvularia geniculata on Poa pratensis

Abstract: Drpo1.tr7irrrt t~fHortic~rrltrr,r. lo11.o Stote Urric~t~r~.sity. Arrrrs. I A , U . S . A . 50011 Hooc;t:s. C. F.. and J . P. M A D S~N . 1979. Leaf senescence as a factor in the competitive and synergistic interactions of Drc,c,lz.sl~~.o .sorokirrirrrltr and Crrrl,rrlorio gerric~rrlotcr on Potr pr.otrrr-.\is. Can. J . Bot. 57: 1706-17 1 I.The competitive and synergistic interactions of Dr.rc~lr.slrra .sorokiriiorro and Cr~r~rrlor~irr grrlit,rrloto on pathogenesis of leaf spot was evaluated on sequentially sene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
2
4
0
Order By: Relevance
“…are weak pathogens that may be part of disease complexes. The current study supports conclusions of Muchovej and Couch (13) and Hodges and Madsen (7,8) that Curvularia spp. are efficient colonizers of senescing tissue (which may be induced by mowing or high temperatures), but do not cause disease symptoms in non-stressed turfgrass and thus should be considered as senectophytes, as defined by Couch (4).…”
Section: Senectopathic Versus Pathogenic Speciessupporting
confidence: 92%
See 2 more Smart Citations
“…are weak pathogens that may be part of disease complexes. The current study supports conclusions of Muchovej and Couch (13) and Hodges and Madsen (7,8) that Curvularia spp. are efficient colonizers of senescing tissue (which may be induced by mowing or high temperatures), but do not cause disease symptoms in non-stressed turfgrass and thus should be considered as senectophytes, as defined by Couch (4).…”
Section: Senectopathic Versus Pathogenic Speciessupporting
confidence: 92%
“…Curvularia spp. have been shown to be stronger saprophytic colonizers than Bipolaris spp., particularly at higher temperatures (7,8). Thus, Curvularia spp.…”
Section: Senectopathic Versus Pathogenic Speciesmentioning
confidence: 95%
See 1 more Smart Citation
“…The disease severity is higher under heat stress, excessive rainfall, pest attack, compacted soil and poor drainage conditions. Hodges et al, 1979 reported that Curvularia spp. are only associated with more severe disease problems at higher temperatures (> 25°C) or when plant tissue is older and/or senescent.…”
Section: Symptoms and Prevalence Of The Diseasementioning
confidence: 99%
“…Leaf spot is progressively more severe on pots. Plants were grown in the greenhouse under l6 hr oflight daily sequentially older leaves of P. pratensis (8)(9)(10). Application of l0-4…”
Section: B) May Be Stimulated or Inhibited By Chlorophenoxymentioning
confidence: 99%